2006
DOI: 10.1111/j.1365-2095.2006.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lysine requirement of juvenile gilthead seabream Sparus aurata L.*

Abstract: The dietary lysine requirement of juvenile gilthead seabream was determined by the growth response of duplicate groups of fish (3.5 g initial weight) fed on six isonitrogenous (427 g kg−1) and isolipidic (135 g kg−1) diets containing graded levels of crystalline l‐lysine HCl, with dietary lysine content ranging from 36.3 to 79.7 g kg−1 of protein. The final indispensable amino acid profile of the diets except for lysine was formulated so as to resemble that of wild seabream whole body. Except for the reduced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 45 publications
4
30
2
3
Order By: Relevance
“…Assim, a eficiência de retenção de proteína ou de nitrogênio e a deposição protéica corporal têm sido recomendadas como principais critérios de resposta na determinação das exigências dietéticas em aminoácidos (Rudehutscord et al, 1997;Tibaldi & Tulli, 1999;Marcouli at al., 2006).…”
Section: Resultsunclassified
“…Assim, a eficiência de retenção de proteína ou de nitrogênio e a deposição protéica corporal têm sido recomendadas como principais critérios de resposta na determinação das exigências dietéticas em aminoácidos (Rudehutscord et al, 1997;Tibaldi & Tulli, 1999;Marcouli at al., 2006).…”
Section: Resultsunclassified
“…In line with the present study, dietary lysine requirements of rainbow trout have been reported to be 2.23 (5.3) % of diet (dietary protein) by Ogino (1980) and 2.32 (6.63) % by Rodehutscord et al (1997) based on the growth performance. Also, results of the present study were similar to those reported for several other species, such as grass carp Ctenopharyngodon idella (2.24 % of diet) (Wang et al 2005) and cobia Rachycentron canadum (2.33 %) (Zhou et al 2007), but higher than those reported for Japanese flounder Paralichthys olivaceus 1.97-2.16 % and red sea bream Pagrus major 2.09-2.14 % (Forster and Ogata 1998), red drum Sciaenops ocellatus 2.0 % Seven experimental diets were formulated to have graded levels of lysine (0.72, 1.12, 1.52, 1.92, 2.32, 2.72 or 3.52 %); equal amount of aspartic acid and glutamic acid by weight were substituted for the proper amounts of lysine in the basal diet (Brown et al 1988), milkfish Chanos chanos 2.0 % (Borlongan and Benitez 1990) and gilthead seabream Sparus aurata 2.15 % (Marcouli et al 2006) and lower than those reported for Japanese seabass 2.49 % ) and grouper Epinephelus coioides 2.83 % (Luo et al 2006). The wide variation observed in the requirements for lysine among fish species may be due to the differences in dietary protein sources, the amino acid pattern (Forster and Ogata 1998), diet formulation, size and age of fish, genetic differences, feeding practices and rearing conditions (Ruchimat et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, é importante na síntese de carnitina, que atua no transporte de ácidos de cadeia longa (WALTON; COWEY, ADRON, 1984). A suplementação de lisina em dietas para peixes está relacionada com o aumento no ganho de peso, melhoria na conversão alimentar, aumento na retenção de nitrogênio e redução no conteúdo corporal de lipídios do salmão do Atlântico, Oncorhynchus mykiss (BERGE; SVEIER; LIED, 1998), tilápia-do-Nilo, Oreochromis niloticus (FURUYA et al, 2006) e Gilthead sea bream, Sparus aurata (MARCOULI et al, 2006 Os peixes foram alimentados com rações contendo 28% de proteína digestível e 3.454 kcal/ kg de energia digestível de forma a atender às exigências para tilápias (FURUYA et al, 2005;FURUYA, 2010) com 0,88; 1,12; 1,36; 1,59 e 1,83% de lisina digestível (base na matéria natural), sendo a arginina suplementada de forma a manter a relação arginina:lisina de 1,43:1 da dieta (Tabela 1).…”
Section: Introductionunclassified